MENERAPKAN MODEL PEMBELAJARAN KOOPERATIFTIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKANHASIL BELAJAR IPS KELAS IVB SDN 011 BUKIT GAJAHKECAMATAN UKUI KABUPATEN PELALAWAN - Asriati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on the researcher’s teaching experience in class IVB at SDN 011 Bukit Gajah, Ukui District, Pelalawan Regency, the learning outcomes of social studies (IPS) had not yet met the expected mastery standards. The minimum mastery criterion (KKM) was set at 70; however, only 12 students were able to achieve the KKM, while the remaining 10 students had not yet met the predetermined standard. Therefore, a learning method was needed that could facilitate students in gaining learning experiences and provide greater opportunities for them to develop according to their abilities. The purpose of this research was to improve IPS learning outcomes of class IVB students at SDN 011 Bukit Gajah, Ukui District, Pelalawan Regency, through the implementation of the cooperative learning model Numbered Heads Together (NHT). This study was conducted as a classroom action research (PTK). The research data showed that students’ daily test results increased from the initial average score of 60.78 to 77.5 in the first daily test (UH I), representing an increase of 18.09%. IPS learning outcomes from the base score to the second daily test (UH II) also increased, from 60.78 to 83.28, an improvement of 37.02%. In addition, teacher activities improved in each meeting, increasing from 58.33% in the first meeting of the first cycle to 87.5% in the last meeting of the second cycle. Student activities also showed improvement, increasing from 58.33% in the first meeting of the first cycle to 83.33% in the final meeting of the second cycle.